Platelet transfusion in pregnancy: clinical profile and pregnancy outcome - Khatuja, Ritu; Jain, Geetika; Radhakrishnan, Gita; Grover, Anshul; Singh, Bharat (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Thrombocytopenia, being second important hematological disorder of pregnancy can result in maternal and neonatal morbidity and mortality in some women. Some of these disorders are not associated with adverse pregnancy outcomes while in others it is associated with maternal and neonatal morbidity and mortality. So this study was conducted to evaluate the various causes of thrombocytopenia associated with platelet transfusion and its effect on maternal and neonatal outcome. Methods: It is a retrospective data analysis of 70 peripartum women admitted in a tertiary level hospital with thrombocytopenia, requiring platelet transfusion over a period of 9 months (January 2013 to September 2013). Patients were analyzed for the cause of thrombocytopenia, requirement of platelet transfusion, additional treatment, duration of hospital stay and maternal and neonatal morbidity and mortality. Results: In this study, pre-eclampsia and HELLP was present in 37.1% (n=26) of women requiring platelet transfusion while obstetrical hemorrhage (APH, PPH and Rupture uterus), combined iron deficiency anemia and infective causes accounted for 27.1% (n=19), 17.1% (n=12) and 15.7% (n=11) of women respectively. One case each of APLA and idiopathic thrombocytopenia was seen. 70% of women had to stay in hospital for more than 5 days. Four women expired and the incidence of morbidities was 73.1%. Prematurity was present in 41.1% neonates and three expired in nursery. Neonatal morbidity and mortality was not affected by maternal thrombocytopenia. Conclusions: Thrombocytopenia associated with pathological conditions like HELLP, dengue and malaria were associated with profound maternal and neonatal morbidity.